MEDIATION AS A CONSTRUCTIVE METHOD AND PREVENTIVE PSYCHOLOGICAL TOOL FOR CREATING A CULTURE OF DIALOGUE AND PREVENTING CONFLICT BEFORE ESCALATION - Dimitrova, Stefka (E-Journal VFU, 2025)
This analysis argues that mediation should be conceptualized not as a reactive measure for escalated conflicts, but as a strategic preventive tool. Its early integration into organizational culture exerts a transformative effect, converting tension into constructive dialogue, reducing the hidden costs of conflicts, and enhancing team resilience. Key arguments reveal that intervention in the initial stages of conflicts—characterized by passive aggression or communication deficits—leads to an 80% reduction in resource expenditure. Systematic mediation practices, including regular feedback, active listening training, and consultations, catalyze cultural change. This shift is empirically confirmed by a 40% decline in disciplinary procedures within organizations employing internal mediators.
Keywords: mediator; conflicts; organization; psychological aspects; workplace conflicts